Emergence of non-albicans Candida among candidal vulvovaginitis cases and study of their potential virulence factors, from a tertiary care center, North India - Varsha Kumari; Tuhina Banerjee; Pankaj Kumar; Sulekha Pandey; Ragini Tilak (Wolters Kluwer Medknow Publications, 2013)
Purpose: The purpose of this study was to determine the prevalence of various Candida species and study some of their virulence factors among thevulvovaginal candidiasis(VVC)patients. Study Design and Settings: The study was conducted in a Tertiary Care University Hospital in North India. Materials and Methods: This study was carried out prospectively for a period of 1 year. High vaginal swabs (HVSs) were collected from women in childbearing age group attending the gynecology and obstetrics out-patient departments with the complaints suggestive of vulvovaginitis. Samples were plated on Sabouraud's dextrose agar slope. Candida spp. isolated was further speciated based on microscopy, biochemical tests and culture characteristics on special media. Virulence factors of these strains were determined by biofilm formation and phospholipase activity. Result: A total of 464 HVS from 232 patients with the complaints of vulvovaginitis were included in this study. Following laboratory workup, 71 specimens were positive for genus Candida (30.6%). Further speciation showed 32.4% as Candida albicans, 45.07% Candida parapsilosis and 22.53% of Candida glabrata. Biofilm production was shown by 50 candidal strains (70.4%) and phospholipase activity was given by 41 candidal strains (57.74%). Conclusion: Our study suggests increasing prevalence of non-albicans Candida among the VVC cases along with their virulence factors. Therefore, we recommend that microbiological investigation upto species level should be mandatory to determine the emergence of non-albicans Candida as a major cause of VVC.